Pharmacological Inhibition of Protein Kinase G1 Enhances Bone Formation by Human Skeletal Stem Cells Through Activation of RhoA-Akt Signaling. (23rd April 2015) - Jafari, Abbas; Siersbaek, Majken S.; Chen, Li; Qanie, Diyako; Zaher, Walid; Abdallah, Basem M.; Kassem, Moustapha
Abstract: Development of novel approaches to enhance bone regeneration is needed for efficient treatment of bone defects. Protein kinases play a key role in regulation of intracellular signal transduction pathways, and pharmacological targeting of protein kinases has led to development of novel treatments for several malignant and nonmalignant conditions. We screened a library of kinase inhibitors to identify small molecules that enhance bone formation by human skeletal (stromal or mesenchymal) stem cells (hMSC). We identified H-8 (known to inhibit protein kinases A, C, and G) as a potent enhancer of ex vivo osteoblast (OB) differentiation of hMSC, in a stage- and cell type-specific manner, without affecting adipogenesis or osteoclastogenesis. Furthermore, we showed that systemic administration of H-8 enhances in vivo bone formation by hMSC, using a preclinical ectopic bone formation model in mice. Using functional screening of known H-8 targets, we demonstrated that inhibition of protein kinase G1 (PRKG1) and consequent activation of RhoA-Akt signaling is the main mechanism through which H-8 enhances osteogenesis. Our studies revealed PRKG1 as a novel negative regulator of OB differentiation and suggest that pharmacological inhibition of PRKG1 in hMSC implanted at the site of bone defect can enhance bone regeneration. Stem Cells 2015;33:2219–2231